Protein nanoparticles in molecular, cellular, and tissue imaging - Kaku, Tanvi Sushil (2022)
The quest to develop ideal nanoparticles capable of molecular, cellular, and tissue level imaging is ongoing. Since certain imaging probes and nanoparticles face drawbacks such as low aqueous solubility, increased ROS generation leading to DNA damage, apoptosis, and high cellular/organ toxicities, the development of versatile and biocompatible nanocarriers becomes necessary. Protein nanoparticles (PNPs) are one such promising class of nanocarriers that possess most of the desirable properties of an ideal nanocarrier for bioimaging applications. PNPs demonstrate high aqueous solubility, minimal cytotoxicity, and multi-cargo loading capacity. They are also amenable to surface-functionalization, as well as modulation of their hydrophobicity and hydrophilicity. The use of PNPs for bioimaging applications has made rapid advancements in the past two decades. Being comparatively less explored, the field opens up a plethora of opportunities and focus areas to engineer ideal bioimaging protein nanocarriers. The use of PNPs as carriers of their natural ligands as well as other heavy metals and fluorescent probes, along with drug molecules for combined theranostic applications has been reported. In addition, surface functionalization to impart specificity of targeting the PNPs has been shown to reduce nonspecific cellular interactions, thus reducing systemic toxicity. PNPs have been explored for their application in imaging of numerous cancers, cardiovascular diseases as well as imaging of the brain using near infrared fluorescence (NIRF) imaging, magnetic resonance imaging (MRI), X-ray computed tomography (CT), positron emission tomography (PET), single-photon emission computed tomography (SPECT), ultrasound (US), and photoacoustic (PA) imaging.